Bacteriostatic Activity and Resistance Mechanism of Artemisia annua Extract Against Ralstonia solanacearum in Pepper - Tiantian Du; Weiping Zhu; Chenning Zhang; Xiaomin Liang; Yinghua Shu; Jingyun Zhou; Mengyu Zhang; Yuxuan He; Jincai Tu; Yuanjiao Feng (Plants)
The destructive bacterial wilt disease caused by Ralstonia solanacearum leads to substantial losses in pepper production worldwide. Plant-derived pesticides exhibit advantages of high efficiency and broad spectrum when compared to traditional chemical pesticides. Artemisia annua and ‘Tai Jiao’ No. 1 were used as the experimental materials, and treated with 0.75 g·mL−1, 1.5 g·mL−1, and 3 g·mL−1 of A. annua extract and inoculated with R. solanacearum at a concentration of OD600 = 0.1 for 14 days. The inhibitory activity of A. annua extracts against R. solanacearum, as well as the disease index, defense enzyme activities, and defense-related substances contents of pepper seedlings were determined. The results showed that the Minimum Inhibitory Concentration (MIC) of the A. annua extract was 3 g·mL−1. As the concentration of A. annua extract increased, the extent of R. solanacearum cell crumpling intensified, accompanied by a gradual decline in its biofilm-forming ability. On the 14th day after treatment, the disease severity index and incidence rate were significantly reduced when the A. annua extract was applied at concentrations of 0.75 g·mL−1 and 3 g·mL−1. At both the 7th and 14th days after treatment, the application of A. annua extract at concentrations of 0.75 g·mL−1 and 3 g·mL−1 led to enhanced activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) in peppers at different stages. Simultaneously, it reduced the levels of malondialdehyde (MDA) and hydrogen peroxide (H2O2), effectively scavenging reactive oxygen species and alleviating cellular lipid peroxidation. Furthermore, the extract increased the activities of polyphenol oxidase (PPO) and phenylalanine ammonia-lyase (PAL), as well as elevated the contents of soluble protein, flavonoids, and total phenols, ultimately enhancing the disease resistance of peppers. Considering the development costs, the application of A. annua extract at a concentration of 0.75 g·mL−1 demonstrates great potential for green control measures against bacterial wilt in peppers.